The Ideal Voting Interface: Classifying Usability - Damien Mac Namara (JeDEM - eJournal of eDemocracy & Open Government, 2014)
This work presents a feature-oriented taxonomy for commercial electronic voting machines, which focuses on usability aspects. Based on this analysis, we propose a ‘Just-Like-Paper’  (JLP) classification method which identifies five broad categories of eVoting interface. We extend the classification to investigate its application as an indicator of voting efficiency and identify a universal ten-step process encompassing all possible voting steps spanning the twenty-six machines studied. Our analysis concludes that multi-functional and progressive interfaces are likely to be more efficient versus multi-modal voter-activated machines.